Optical fiber microbend pressure sensor , base on optical time domain reflectrometer technique - Lhaten, Lhaten (2012)
Much research have been done for the past few decades on distributed sensor and also on the fabrication of optical fibre sensor for detection of vibration, cracks on buildings and other environmental parameters. Due to the fact that fibre optic sensors are small, and immune to electromagnetic fields, it is the preferred choice for applications in hazardous, explosive and harsh environment. In this study, the transmission loss due to pressure on an optical fiber was measured using a commercial optical time domain reflectometer (OTDR) to determine the sensor sensitivity. A multimode optical fiber (50/125) was subjected to pressure using various mass in the range of 500 g to 2000 g at 25 m, 50 m and 75 m from the end of the fiber. The mass was placed on the fiber using microbend test rigs (referred to as sensor) of area 910 x 10-6 m2 with corrugation periodicity of 2 mm for sensor I and 1.6 mm for sensor II. Optical signal of 1300 nm from the OTDR was transmitted along an optical fiber of length of 1173.5 m. The optical output was analyzed using OTDR trace viewer 4.1 and the losses were determined by two point, least square fit and combination methods. The transmission loss increases with pressure and changes with sensor location. The sensor sensitivity was determined for each method as the average slope of the loss-pressure graph. The sensor sensitivity for sensor II was higher than sensor I determined by combination method. Thus the sensor II is more sensitive than sensor I due to more microbending. The sensitivity of the sensors can be higher if it has low and fine corrugation periodicity. The combination method was found out to be the suitable method to determine the sensor sensitivity as it is easy and accurate to analyse the loss and convenient to place the markers on the OTDR trace.